Availability of telehealth-based services at syringe services programs under the COVID-19 Public Health Emergency - Tyler S. Bartholomew; Hansel E. Tookes; Teresa A. Chueng; Ricky N. Bluthenthal; Lynn D. Wenger; Alex H. Kral; Barrot H. Lambdin (BMC, 2023)
Abstract Introduction The expanded capacity of syringe services programs (SSPs) in the USA to integrate telehealth services was largely related to flexibility of buprenorphine prescription in response to the COVID-19 pandemic. SSPs demonstrated the potential of using telehealth to reach participants with both medical and non-medical services. The present study examines the implementation of medical and non-medical telehealth-based health services in 2020 at SSPs in the USA and organizational characteristics associated with adopting specific telehealth services. Methods We administered a cross-sectional survey among all known SSPs operating in the USA as of 2021. The two primary study outcomes were (1) implementation of medical telehealth and (2) implementation of non-medical telehealth in 2020. Medical services included HIV counseling/care, hepatitis C virus (HCV) counseling/care, and buprenorphine. Non-medical services included wellbeing/check-ins, overdose prevention training, health navigation, harm reduction and psychological counseling. Bivariate and multivariable mixed effects logistic regression models were used to directly estimate the odds ratio associated with organizational characteristics on the implementation of telehealth-based health services. Results Thirty percent of programs (n = 290) reported implementing telehealth-based health services. In multivariable logistic regression models, community-based organization SSPs had higher odds of implementing medical (aOR = 4.69, 95% CI [1.96, 11.19]) and non-medical (aOR = 2.18, 95% CI [1.10, 4.31]) health services compared to public health department SSPs. SSPs that received governmental funding had higher odds of implementing medical services via telehealth (aOR = 2.45, 95% CI [1.35, 4.47]) compared to programs without governmental funding. Conclusion Community-based organization SSPs and those with government funding had the highest odds of telehealth implementation in response to the COVID-19 Public Health Emergency. Federal, state, and local governments must increase funding for low-barrier venues like SSPs to support telehealth implementation to serve the needs of people who use drugs.